Analysis of variability of quantitave traits of Vaccinium corymbosum L. ex vitro under different lighting modes - Fedorenko, Marta P.; Volotovich, Anton A.; Kudryashova, Oksana A. (Experimental Biology and Biotechnology, 2019)
The article presents the results of studies on the comparative analysis of bioproductional parameters of plant growth of Bluecrop and Elizabeth high-bush blueberry ex vitro under the conditions of fluorescent and LED lighting. Ensuring the optimal spectral composition of radiation, realized with the original LED light, led to a significant increase at 1.1–1.6 times in all of the analyzed growth parameters in high-bush blueberry ex vitro plants.
Keywords: clonal micropropagation; LED lighting; high-bush blueberry; ex vitro; Bluecrop; Elizabeth